Adverse drug reactions in the emergency department: Is there a role for pharmacogenomic profiles at risk?— Results from the ADRED study - Just, Katja S.; Dormann, Harald; Schurig, Marlen; Böhme, Miriam; Fracowiak, Jochen; Steffens, Michael; Scholl, Catharina; Seufferlein, Thomas; Gräff, Ingo; Schwab, Matthias; Stingl, Julia C. (Journal of Clinical Medicine, 2020)
Individual differences in required drug dosages exist based on the pharmacogenomic (PGx) profiles. This study aimed to assess associations between PGx profiles and adverse drug reactions (ADR) that lead to admissions to the emergency department (ED). ADR cases of the prospective multi-center observational trial in EDs (ADRED study) were analyzed (n = 776) together with the relevant PGx phenotypes of the enzymes CYP2D6, CYP2C19, CYP2C9, and VKORC1. Overall, the allele frequency distribution in this cohort did not differ from the population frequencies. We compared the frequencies of phenotypes in the subgroups with the drugs suspected of certain ADR, in the remaining cases. The frequency distribution of CYP2C19 differed for the ADR bleeding cases suspected of clopidogrel (p = 0.020). In a logistic regression analysis, higher CYP2C19 activity (OR (95% CI): 4.97 (1.73−14.27)), together with age (1.05 (1.02−1.08)), showed an impact on the clopidogrel-suspecting ADRs, when adjusting for the clinical parameters. There was a trend for an association of phenprocoumon-risk profiles (low VKORC1 or CYP2C9 activity) with phenprocoumon-suspecting ADRs (p = 0.052). The PGx impact on serious ADRs might be highest in drugs that cannot be easily monitored or those that do not provoke mild ADR symptoms very quickly. Therefore, patients that require the intake of those drugs with PGx variability such as clopidogrel, might benefit from PGx testing.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Adverse drug reactions; Clopidogrel; CYP2C19; Pharmacogenomics; Phenprocoumon